2013
DOI: 10.1186/1471-2164-14-706
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping and expression analysis of miRNAs and their target genes during fiber development in cotton

Abstract: BackgroundMicroRNAs (miRNAs) are small, endogenously expressed, non-coding RNA molecules involved in gene transcription and expression that combine with specific mRNA site of target genes to inhibit protein synthesis or degrade mRNA. Since the first plant miRNA was reported in 2002, numerous new miRNAs and their targets have been discovered via high-throughput sequencing and computational approaches. However, the genetic variation of miRNA genes is poorly understood due to the lack of miRNA-specific DNA marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Overall, the result provided a good data resource for better understanding of fibre development. Several other studies also show that many miRNAs were differentially expressed during cotton fibre initiation and development ( Pang et al , 2009 ; Chen et al , 2013 ; Gong et al , 2013 ; Zhang et al , 2013 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, the result provided a good data resource for better understanding of fibre development. Several other studies also show that many miRNAs were differentially expressed during cotton fibre initiation and development ( Pang et al , 2009 ; Chen et al , 2013 ; Gong et al , 2013 ; Zhang et al , 2013 ).…”
Section: Discussionmentioning
confidence: 80%
“…MicroRNAs (miRNAs) may play a role during cotton response to drought and salinity stress. Using both computational and deep sequencing technology, some conserved and new miRNAs have recently been identified in cotton ( Qiu et al , 2007 ; Zhang et al , 2007 ; Pang et al , 2009 ; Chen et al , 2013 ; Gong et al , 2013 ; Yang et al , 2013 ; Zhang et al , 2013 ). Some of these miRNAs and their predicted targets were also found to be expressed differentially in terms of dose dependence and tissue dependence under salinity and drought conditions, such as miR156-SPL2, miR162-DCL1, miR159-TCP3, miR395-APS1, and miR396-GRF1 ( Yin et al , 2012 ; Wang et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2014) identified 54 miRNAs including 47 conserved and 7 new miRNAs from island cotton using deep sequencing; their study also show that miR160, miR167, miR171, miR172 and miR827 were highly expressed in fiber initiation stage comparing to the elongation and secondary wall biosynthesis stage 37 . At the same time, several laboratories reported hundreds of miRNAs in cotton ovules and fibers 25 , 38 40 . Xie et al (2015) identified 65 conserved miRNA families in cotton ovules with initiated fiber and leaves using the first-generation deep sequencing technology; among these miRNAs, the expression of 32 miRNA families were difference between ovule and leaf tissues 41 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are class of RNAs which do not take part in protein coding having short length from 18 to 26 nucleotide (nt) long. Chen et al, (2013) revealed that long hairpin precursor is processed to produce mature miRNA sequence. The gene expression is regulated by miRNAs via messenger RNA's (mRNA) decomposition or translation (Khvorova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%